THE INFLUENCE OF THE STRUCTURE OF INTERINDUSTRIAL LINKAGES OF THE ECONOMY ON ITS CAPACITY TO ADOPT INNOVATIONS - K. KHALMETSKI (Advanced Engineering Research, 2006)
The paper considers technological structure of the economy as a factor of the country’s absorptive capacity. The work is based upon the statistical analysis of the main developed countries. The author reveals a regularity, which connects the structure of the interindustrial linkages with its capacity to adopt foreign technologies, firstly from the foreign direct investment. The model is based upon the newest theoretical works in organizational learning theory and interindustrial linkages. The results can be applied by investigations of international technological diffusion, as well as by arranging the priority directions of attracting foreign direct investment.